2006
DOI: 10.1038/sj.bdj.4813590
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the perceived effects on Scottish general dental practitioners of peer review and other continuing professional development

Abstract: Aim To produce evidence to inform future provision of continuing professional development (CPD). Method A postal questionnaire survey of 268 dentists who had participated in the pilot peer review scheme in Scotland. Results Courses, both Section 63 and privately run, were both seen as highly effective in changing both knowledge and practising behaviour. Most of the free form comments invited were positive about the effects and acceptability of peer review as a mode of CPD. Courses and reading journals were fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…In contrast, older dentists are fewer in number and nearing retirement. Several studies have reported that both of these groups feel that continuing education had the least impact on their practices [5, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, older dentists are fewer in number and nearing retirement. Several studies have reported that both of these groups feel that continuing education had the least impact on their practices [5, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…Dentists in Scotland, where CPD is mandatory, felt that shorter courses were an effective and well-liked way of producing change in their dental practices [10]. Time constraints imposed by busy private practice were a limiting factor affecting attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Courses have been found to be effective in improving knowledge and understanding (93,94). Based on a survey of dentists in Scotland, Maidment (94) reported that courses and reading journals were both thought to be better for enhancing knowledge whilst other modes of CPD were better at changing practice.…”
Section: Redwood Winning Et Al (61)mentioning
confidence: 99%
“…Based on a survey of dentists in Scotland, Maidment (94) reported that courses and reading journals were both thought to be better for enhancing knowledge whilst other modes of CPD were better at changing practice. Mercer et al (33) asked GDPs about CPD activities that had impacted on the way they practised.…”
Section: Redwood Winning Et Al (61)mentioning
confidence: 99%
“…It appeared to be having a positive influence on everyday practice in surgeries, for example by encouraging investment in new cross-infection control equip ment and revision of surgery procedures. In this sense, it con forms to Maidment's view 8 that effective adult learning should be both interactive and relevant, whilst building on dentists' own experience. Overall it was well received by the majority of practitioners.…”
Section: Discussionmentioning
confidence: 99%